Some superfluous names recently proposed involving the Sino-Himalayan Anemone rupestris (Ranunculaceae) - Fei, Wen-Qun; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2023)
Based on literature survey, we demonstrate that the name Anemone rupestris Jacquemont ex Cambessedes in the Ranunculaceae has never been validly published and thus has no status in nomenclature. This name is not a later homonym of A. rupestris Wallich ex Hooker & Thomson, the correct name of a widely distributed Sino-Himalayan species. Anemone neorupestris and the four resultant names, A. neorupestris subsp. neorupestris, A. neorupestris subsp. neorupestris var. neorupestris, A. neorupestris subsp. neorupestris var. latifolia and A. neorupestris subsp. gelida, therefore, are all superfluous and illegitimate. In order to prevent their wide use and avoid nomenclatural confusion, we propose to synonymize all these names herein. Lectotypification is proposed for the name A. gelida.